A (IN)EFETIVIDADE DO PRINCÍPIO INTERGERACIONAL NO ESTADO SOCIOAMBIENTAL DE DIREITO À LUZ DO ESTADO DE COISAS INCONSTITUCIONAL EM MATÉRIA AMBIENTAL (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The article looks at the problem of the unconstitutional state of affairs in environmental matters, based on the socio-environmental rule of law and the intergenerational principle. Thus, based on the study of liquid modernity, a term coined by Bauman, together with Ulrich Beck's analysis of risk, a parallel is drawn between the effects of the Industrial Revolution, economic and technological development and exacerbated consumerism in relation to the impacts on the environment today. Using the deductive method, with a bibliographical and literature review, the objective is to analyze the impacts of frenetic consumerism and economic and technological development in liquid modernity, considering that human activity has been marked by predatory conduct and total indifference to environmental protection for present and future generations, which shows that individualism prevails today and actions are disconnected from the principles of intergenerational solidarity and sustainable development, as well as the necessary environmental protection. This demonstrates a state of disconformity between the recurring scenario of environmental degradation, in view of the ideals of capitalism in the face of constitutional precepts, according to the STF's analysis of ADPF 760 and ADO 54.